IJITIHAD OF SULTAN MUHAMMAD IDRUS KAIMUDDIN (1824-1851) IN BUTON, SOUTHEAST SULAWESI, INDONESIA - Basrin Melamba, M.A.; Muarifuddin Muarifuddin (JICSA : Journal of Islamic Civilization in Southeast Asian, 2013)
The introduction of Islam in the Sultanate of Buton has brought about changes in the social, political, and even intellectual aspects of the sultanate. This is observable in the thought of local scholars who try to blend Islam and local culture. One of these figures is Sultan Muhammad Idrus Kaimuddin (1824-1851). The thought of Sultan Muhammad Idrus Kaimuddin finds the essence of its concept of manners or etiquette in the teachings of the ancestors in Bula Kabanti Malino and several works of Sultan Muhammad Idrus Kaimuddin. The guidance of the public and court authorities in the Sultanate of Buton was basically and mostly coming from the teachings of Islam. Thinking in terms of ethics, morals, manners, the advice of Sultan Kaimuddin has deep horizons of knowledge and thought. The magnitude of the influence of Islam in the thought of Muhammad Idrus Kaimuddin evidently works, which proves that the process of acculturation between Islam and Butonese culture runs well. The acculturation between Islam and Butonese culture was essentially a formation process of Butonese civilization centered in the palace and passed on to Buton society in general, through the process of cultural dialogue between Buton (Wolio) and Islam.